Lecturers and Students Perceptions on E-learning Implementation: A Case Study in English Education Study Program - Muhammad Wahyudi; Sofendi Sofendi; Sary Silvhiany (STAI Hubbulwathan Duri, 2023)
E-learning is mostly acknowledged as a type of learning that is facilitated by electronic media typically connected to the internet. It has been continuously promoted as an alternative to adult learners enrolled in higher education, especially during the pandemic outbreak. Upon its implementation, many consider the electronic learning option benefits them, while others argue it raises inconveniences. These opposing views certainly stimulate associated lecturers and learners in English language teaching and learning to give different responses as well. Thus, the exploration of their perceptions towards e-learning implementation is highlighted in this article through a case study carried out at one of the private universities in South Sumatera. The participants were two lecturers and ten students from two different courses. Open-ended questionnaires and interviews were conducted to obtain the data and analysed using thematic analysis. A member checking was done to measure the credibility and control of biases in this study. The findings recapitulate that e-learning was implemented to facilitate three main activities, namely administrative task fulfilment, teaching-learning process, and teaching-learning preparation. Besides, the perceptions from all participants showed that online learning classes generated some benefits and drawbacks.